Digitalized Regional Development Planning Model for North Gorontalo Regency: A Technology-Enhanced Approach to Participatory and Technocratic Planning - Indah, Nurmala Suci; Rachman, Ellys; Gobel , Lisda Van (Journal of Scientific Insights, 2024)
The objectives of this study are: (1) To find out and analyze the regional development planning model by the Regional Planning Research and Development Agency of North Gorontalo Regency seen from the technocratic planning model, participatory planning, and top-down and bottom- up planning, (2) To find out and analyze the inhibiting factors of the regional development planning model by the Regional Planning Research and Development Agency of North Gorontalo Regency. This study uses a qualitative approach with a descriptive research type. The data consists of primary data obtained from interviews with informants and observations and secondary data from document studies. The results of the study indicate that the regional development planning model of technocratic planning, namely regional development planning is formulated based on the results of analysis by competent regional apparatus and academics and has a function as an implementing team for the preparation of the RKPD, Participatory planning, namely BAPPPEDA coordinating with other agencies and presenting community leaders in accommodating community aspirations and proposals fairly in supporting regional development in North Gorontalo Regency, while top-down and bottom-up planning, namely planning through musrenbangda by synchronizing government work plans and program proposals from the community. Furthermore, the inhibiting factors of the planning model due to limited human resources that are not yet sufficient and inadequate, community program proposals have not been fully realized due to lack of community knowledge in development planning, lack of consistency in top-down and bottom- up planning due to lack of awareness and community involvement in the planning process.